Wild-Type and Mutant FUS Expression Reduce Proliferation and Neuronal Differentiation Properties of Neural Stem Progenitor Cells - Stronati, Eleonora (Int J Mol Sci, 2021)
Nervous system development involves proliferation and cell specification of progenitor cells into neurons and glial cells. Unveiling how this complex process is orchestrated under physiological conditions and deciphering the molecular and cellular changes leading to neurological diseases is mandatory. To date, great efforts have been aimed at identifying gene mutations associated with many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Mutations in the RNA/DNA binding protein Fused in Sarcoma/Translocated in Liposarcoma (FUS/TLS) have been associated with motor neuron degeneration in rodents and humans. Furthermore, increased levels of the wild-type protein can promote neuronal cell death. Despite the well-established causal link between FUS mutations and ALS, its role in neural cells remains elusive. In order to shed new light on FUS functions we studied its role in the control of neural stem progenitor cell (NSPC) properties. Here, we report that human wild-type Fused in Sarcoma (WT FUS), exogenously expressed in mouse embryonic spinal cord-derived NSPCs, was localized in the nucleus, caused cell cycle arrest in G1 phase by affecting cell cycle regulator expression, and strongly reduced neuronal differentiation. Furthermore, the expression of the human mutant form of FUS (P525L-FUS), associated with early-onset ALS, drives the cells preferentially towards a glial lineage, strongly reducing the number of developing neurons. These results provide insight into the involvement of FUS in NSPC proliferation and differentiation into neurons and glia.